2016
DOI: 10.1002/fsn3.402
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient content of fish powder from low value fish and fish byproducts

Abstract: Consuming small‐sized fish species whole, and bones of large fish could contribute significantly to reducing the level of micronutrient and protein malnutrition. These fish products are more affordable and could therefore meet the needs of poor, vulnerable groups, particularly in rural and urban areas where limited economic resources prevent dietary diversity. The objectives of the study were to produce fish powder from dried edible byproducts from fish processing factories, an underutilized fish species, burr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
48
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 2 publications
8
48
0
2
Order By: Relevance
“…One study [30] showed that such variation in concentrations of mineral elements from one species to another was due to the chemical forms of the elements and their concentrations in the local environment. Another study [31] reported that Burrito fish (Brachydeuterus auritus) contains 93.71 mg/100 g phosphorus which is near to the present study. Such low concentration of phosphorus might be due to the removing of head, bones and scales from the fish body.…”
Section: Phosphorus Contentsupporting
confidence: 84%
“…One study [30] showed that such variation in concentrations of mineral elements from one species to another was due to the chemical forms of the elements and their concentrations in the local environment. Another study [31] reported that Burrito fish (Brachydeuterus auritus) contains 93.71 mg/100 g phosphorus which is near to the present study. Such low concentration of phosphorus might be due to the removing of head, bones and scales from the fish body.…”
Section: Phosphorus Contentsupporting
confidence: 84%
“…The change in Fe content after processing was found to be significant ( p  < 0.05). Recommended dietary intake (RDI) of iron for children 9–13 years/day is 8 mg (Abbey et al, 2017). Hence, consumption of B. nurse powder could adequately meet the iron needs of children in these age brackets.…”
Section: Resultsmentioning
confidence: 99%
“…The reported lipid content of Catfish frame (Bechtel et al, ), when converted to similar moisture content, was 42 percent, similar to the 41 percent in this study. Lipid content of tuna frame (prepared similarly to the Catfish raw frame in Table ) was reported as 11 percent (Abbey, Glover‐Amengor, Atikpo, Atter, & Toppe, ) or 27 percent (Istiqlaal, ), and for Pollock and Cod, values of 4 and 3 percent were reported (after conversion to 4 percent moisture; Bechtel, )—much lower than the 41 percent in these Catfish samples. In comparison with the treated Catfish frame (1.53 percent lipid), cleaned bones (head and frame) from Cod and Blue whiting had a lipid content of 1.14 and 4.91 percent, respectively, but Salmon and Trout had 38.12 and 34 percent, respectively (Toppe et al, ).…”
Section: Resultsmentioning
confidence: 92%
“…Protein content of the raw frame (33 percent) was very similar to that reported for Catfish frame (converted to a moisture content of 13.8 percent) with 34 percent (Bechtel et al, ). Raw Tuna frame is reported to have 29 percent protein (Abbey et al, ) or 9 percent (Istiqlaal, ). Protein content of cleaned bone (head and frame) of Cod and Blue whiting was reported as 36 and 42 percent, respectively, and Salmon and Trout had 29 and 31 percent, respectively (Toppe et al, ), compared to the 33 percent found for Catfish in this report.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation